1989
DOI: 10.3109/00365528909089248
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Assessment of Gastrointestinal Side Effects Induced by Non-Steroidal Anti-Inflammatory Drugs: Endoscopic Lesions, Faecal Blood Loss, and Symptoms Not Necessarily Correlated, As Observed after Naproxen and Oxindanac in Healthy Volunteers

Abstract: Gastrointestinal side effects caused by naproxen and oxindanac (a developmental non-steroidal anti-inflammatory drug) were compared by combined endoscopy and determination of faecal blood loss in 16 healthy male volunteers in a randomized, double-blind, crossover study. Individual daily faecal blood loss was determined by means of 51Cr-labelled erythrocytes. Gastroduodenoscopy was performed before and after administration of naproxen, 750 mg/day, and oxindanac, 600 mg/day, for 1 week each. A washout period of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 18 publications
(12 reference statements)
1
6
0
Order By: Relevance
“…Also, EP-4-deficient mice were shown to develop severe colitis (33), in agreement with the observation that nonsteroidal anti-inflammatory drugs often trigger and exacerbate inflammatory bowel disease in humans (34). These studies suggest an anti-inflammatory role for PGE 2 , in agreement with previously reported antiproliferative effects on activated T cells (reviewed in Ref.…”
Section: Endritic Cells (Dc)supporting
confidence: 90%
“…Also, EP-4-deficient mice were shown to develop severe colitis (33), in agreement with the observation that nonsteroidal anti-inflammatory drugs often trigger and exacerbate inflammatory bowel disease in humans (34). These studies suggest an anti-inflammatory role for PGE 2 , in agreement with previously reported antiproliferative effects on activated T cells (reviewed in Ref.…”
Section: Endritic Cells (Dc)supporting
confidence: 90%
“…A number of studies have reported that prescription dosage level ibuprofen produces time and dose-dependent blood loss (assessed using the radiochromium blood loss technique) from the GI tract of volunteers or patients (Warrington et al 1982;Aabakken et al 1989;Hunt et al 2000) and mild-moderate endoscopic changes in fasted human volunteers (Lanza et al 1979(Lanza et al , 1981(Lanza et al , 1987Friedman et al 1990;Bergmann et al 1992;Roth et al 1993;Müller et al 1995;Gallego-Sandin et al 2004) or those with rheumatic diseases (Teixeira et al 1997). The extent of the loss of blood maybe overestimated using the radiochromium technique as a consequence of biliary excretion of the radiolabelled chromium (Schneider et al 1984;Rainsford 2004a).…”
Section: Gastro-intestinal (Gi) Toxicitymentioning
confidence: 97%
“…Those studies (14-17) have only dealt with self-reported GI-symptoms. The lack of correlation between subjective and objective measurements of GI side-effects has previously been reported (3). It might therefore be a real difference between morning and evening dose regarding G I side-effects, but in order to detect this, endoscopic investigations seem t o be needed.…”
Section: Discussionmentioning
confidence: 94%
“…Nonsteroidal antiinflammatory drugs (NSAIDs) represent an important therapy for alleviation of symptoms in osteoarthrosis. One of the main problems of this type of therapy is the tendency towards dyspepsia and gastric ulceration (1)(2)(3). Some NSAIDs are given up to three times daily.…”
mentioning
confidence: 99%